2023
DOI: 10.3390/ma16030979
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Damage Characteristics and Acoustic Properties of Red Sandstone with Different Water Contents under Microwave Radiation

Abstract: Rock breaking is one of the most basic issues in deep underground engineering. Water plays an important role in the rock response under microwave radiation. Consequently, microwave radiation experiments using red sandstone with different water contents were conducted. The damage characteristics and ultrasonic properties of red sandstone after microwave radiation were primarily investigated, and the representative conclusions were drawn as follows: With the increase in water content, the time of complete format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The research findings demonstrated significant variations in the roughness of rock samples associated with different water content. Moreover, the study revealed that different degrees of rock damage occurred due to distinct microwave radiation levels 41 . Wang's research shows that water content is positively correlated with DIF of sandstone 42 44 .…”
Section: Introductionmentioning
confidence: 98%
“…The research findings demonstrated significant variations in the roughness of rock samples associated with different water content. Moreover, the study revealed that different degrees of rock damage occurred due to distinct microwave radiation levels 41 . Wang's research shows that water content is positively correlated with DIF of sandstone 42 44 .…”
Section: Introductionmentioning
confidence: 98%
“…In a series of experiments to examine the pore distribution of sandstones in various saturated water, Zhou and Cai discovered that at identical water content, the sandstone tensile strength differed considerably [25][26][27][28]. Sandstone's fracture penetration rate clearly varies with varying water contents, based on Liu's study of the impact of water content on the damage features of the sandstone [29]. Natural and saturated sandstones were tested with tensile tests by Liu, who discovered that the crack propagation in sandstones began in the center [30].…”
Section: Introductionmentioning
confidence: 99%
“…The large amount of waterbased fracturing fluid in hydraulic fracturing, however, creates water-related problems such as potential impacts on the environment and groundwater, formation damage resulting from capillary retention and clay swelling, and the high level of consumption of freshwater, placing demands on local water supplies. Consequently, to avoid or minimize these waterrelated issues, the research and development into waterless or reduced-water fracturing methods have been active in recent years [1][2][3][4][5]. Cryogenic fracturing has been researched as a potentially effective waterless fracturing method.…”
Section: Introductionmentioning
confidence: 99%